P667 Unmet needs in the management of Inflammatory Bowel Diseases in Egypt. (21st January 2022) - Khorshid, M; Abdel-Gawad, M; AbdAllah, M; Tag-Adeen, M; Afify, S; El Deeb, R; Elshaarawy, O; Elbasiony, M; Bassuny, A N; El-Raey, F; Fathy, H; ElShabacy, O; et al.
Abstract: Background: Despite the progress in the management of inflammatory bowel diseases (IBD), there are still notable unmet needs in middle- and low-income countries. Defining those unmet needs will help improve patients' care and quality of life. In this survey, our objective was aimed at exploring the current practice of physicians managing IBD patients in Egypt and the unmet needs in diagnosis, treatment, and medical education. Methods: A web-based survey was designed. It was sent to clinicians via emails and followed up to track response rate. The survey was composed of six domains collecting demographic data, modalities used to diagnose patients with IBD, barriers, and challenges in managing IBD patients, availability of different diagnostic modalities and complementary specialties and policies to improve IBD care in Egypt, and finally the physicians' needs and challenges in IBD training. Results: Two hundred and eighty-eight physicians completed the survey. The mean age (±SD) was 36.22(±7.40) years and 69.44% were males. Endoscopic findings and histopathological examination were the most commonly used methods for IBD diagnosis (84.72% and 82.29% respectively). The most common challenges to IBD diagnosis in Egypt were the low availability of IBD multidisciplinary teams and non-informative histopathological reports (55.55% and 50.34% respectively). Expensive medications and poor adherence to therapy were the most important patients' factors leading to poor IBD management (78.47% and 72.22% respectively). Physicians strongly preferred clinical rounds and case presentations rather than lectures and web-based learning (61.2 % versus 51.5% and 47.1% respectively). Most participants agreed that developing guidelines for IBD management, increasing IBD research, establishing patient access programs, and increasing IBD awareness among patients were the most important activities needed to Improve IBD care. Conclusion: Lack of multidisciplinary/ complimentary teams, expensive medications, and poor adherence to therapy can lead to poor IBD management in Egypt. Developing guidelines for IBD management, increasing IBD research are urgently needed to Improve IBD patients' care.